Moral Leadership of Middle-Lower Level Managers and Employee’s Job Satisfaction of Divine Word Colleges in Region I, Philippines as Perceived by the Employees - Abun, Damianus; Racoma, Alfie; Racsa, Lilia R. (IJRDO - Journal of Business Management, 2017)
The study was intended to measure the moral leadership of middle-lower level managers of Divine Word Colleges in Region I, Philippines and how it affects the job satisfaction of employees. In order to strengthen the study, theories on moral leadership were presented and related literature and studies were reviewed. The conceptual framework of the study was established on the four variables such as integrity, trust, ethical leadership, and honesty as independent variables and job satisfaction as dependent variable. The framework indicates the relationship of both variables: moral leadership and job satisfaction. Based on the conceptual framework, the statements of the problems were proposed and questionnaires were made. The questionnaires were adopted from the study of Foronda (2010). The study used the descriptive correlational research design and used Pearson r to determine the relationship between moral leadership and job satisfaction. The study found that moral leadership of middle-lower level managers of Divine Word Colleges in Region I, Philippines in terms of integrity, trust, ethical relationship and honesty is very good and that moral leadership correlates to job satisfaction of employees.